Implementasi Nilai-nilai Karakter Siswa melalui Kegiatan Ekstrakurikuler Kepramukaan di SMAN 6 Kota Gorontalo - Moh Rezky Ashari Djafar; Asmun W. Wantu; Ariyanto Nggilu (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to explore in depth the implementation of students' character values through scouting extracurricular activities at SMAN 6 Gorontalo City. The method used is a descriptive qualitative approach, where data were collected through observation, documentation, and in-depth interviews. Data analysis was carried out interactively, including data reduction, data presentation, and drawing conclusions to emphasize the scientific contribution regarding the effectiveness of scouting activities in student moral formation. The results of the study show that the implementation of religious, disciplined, and creative values is carried out through routine habituation such as congregational prayers, strict time management, and utilizing limited facilities as a means for creativity. These findings indicate that scouting activities serve as an effective medium for the internalization of character education contextually and structurally. However, optimizing implementation requires support for school facilities and innovation in training methods from scoutmasters to overcome obstacles such as students' physical exhaustion and infrastructure constraints.